Femtosecond fluorescence and intersystem crossing in rhenium(I) carbonyl-bipyridine complexes - Cannizzo, Andrea; Blanco-Rodríguez, Ana Maria; El Nahhas, Amal; Sebera, Jakub; Zális, Stanislav; Vlcek, Jr, Antonín; Chergui, Majed (Journal of the American Chemical Society, 2008)
Ultrafast electronic-vibrational relaxation upon excitation of the singlet charge-transfer b (1)A' state of [Re(L)(CO) 3(bpy)] ( n ) (L = Cl, Br, I, n = 0; L = 4-Et-pyridine, n = 1+) in acetonitrile was investigated using the femtosecond fluorescence up-conversion technique with polychromatic detection. In addition, energies, characters, and molecular structures of the emitting states were calculated by TD-DFT. The luminescence is characterized by a broad fluorescence band at very short times, and evolves to the steady-state phosphorescence spectrum from the a (3)A" state at longer times. The analysis of the data allows us to identify three spectral components. The first two are characterized by decay times tau 1 = 85-150 fs and tau 2 = 340-1200 fs, depending on L, and are identified as fluorescence from the initially excited singlet state and phosphorescence from a higher triplet state (b (3)A"), respectively. The third component corresponds to the long-lived phosphorescence from the lowest a (3)A" state. In addition, it is found that the fluorescence decay time (tau 1) corresponds to the intersystem crossing (ISC) time to the two emissive triplet states. tau 2 corresponds to internal conversion among triplet states. DFT results show that ISC involves electron exchange in orthogonal, largely Re-localized, molecular orbitals, whereby the total electron momentum is conserved. Surprisingly, the measured ISC rates scale inversely with the spin-orbit coupling constant of the ligand L, but we find a clear correlation between the ISC times and the vibrational periods of the Re-L mode, suggesting that the latter may mediate the ISC in a strongly nonadiabatic regime.